Development of The Solution Focused Brief Counseling (SFBC) to Improve The Autonomy of Vocational School Students - Swandevi, Ni Kadek Ayumi; Suranata, Kadek; Dharsana, I Ketut (Bisma The Journal of Counseling, 2020)
This study was aimed to know the procedure of implementing a solution focused brief counseling to improve student autonomy and to study and validating the contents of guidebook for a solution focused brief counseling model. This type of research is research and development (R&D), the research model using Four-D (4D). The Four-D model consists of four stage of research that is defining, designing, developing, and disseminating. Data analysis to test the validity of the manual book content using the Lawshe CVR and CVI formulas. Tests carried out by 5 experts who are competent in Counseling and Psychological Guidance. The results of the research based on validity analysis of the content are, the CVR values per item obtained between +1 to 0 (CVR> 0). Furthermore, the results of the Lawshe CVI analysis obtained a score of 0.97 greater than 0 (0.97> 0). Based on the analysis of these data, the validity value of the manual book content is high.